Effect of Foot Insole on Planter Pressure Distribution in Patients with Neuropathic Diabetic Foot Ulcer: A Prospective, Randomized, Double-Blinded, Controlled Clinical Trial - Hany M. Elgohary; Ibtsam Allam; Ahmed M. N. Tolba; Faten Ali; Reem M. Alwhaibi; Hoda M. Zakaria; Walaa M. Ragab; Youssef Elbalawy (Medicina)
Background and Objectives: Patients with diabetes polyneuropathy are at a heightened risk for developing foot ulcers, often due to dynamic plantar foot pressure patterns that lead to increased pressure and shear forces in specific foot areas. This study aimed to evaluate the effects of foot insoles on peak pressure and the pressure–time integral in patients with polyneuropathy diabetic foot ulcers over a twelve-week period followed by an eight-week follow up. Materials and Methods: This was a prospective, randomized, double-blinded, controlled clinical trial involving 60 patients aged between 50 and 65 years of both genders. Inclusion criteria included midfoot ulcer grades II or III, a history of polyneuropathy diabetic foot ulcers lasting between six months and one year, diabetes duration of seven to ten years, glycated hemoglobin levels between 7% and 9%, and a body mass index (BMI) ranging from 25 to 30 kg/m2. Participants were randomly assigned to either the study group, which received foot insoles along with medication and wound care, or the control group, which received only medication and wound care. Measurements of peak pressure and pressure–time integrals were taken at the start of this study, after twelve weeks, and again eight weeks post-study. Results: The results indicated significant differences in peak pressure and pressure–time integral measurements for the rearfoot, midfoot, hallux, and both medial and lateral forefoot areas after twelve weeks of using foot insoles compared to the control group. This suggests that the use of foot insoles effectively reduces peak pressure and the pressure–time integral in these critical areas. Conclusions: The findings of this study support the use of foot insoles as a beneficial intervention for decreasing peak pressure and the pressure–time integral on the hallux, medial, and lateral forefoot in patients with polyneuropathic diabetic foot ulcers, and they could play a crucial role in preventing further complications.